The Effects of Audience's Attitudes on Actor, Character, Movie and Product Placement on the Brand Attitude - Elif Ülker-Demirel; Erkan Yıldız (Istanbul Business Research (IBR), 2020)
In recent years, there has been a shift in consumers' media consumption preferences from traditional to digital platforms. Adblocker applications used by consumers who do not want to be exposed to advertising and the digital platforms that offer ad-free content make it increasingly difficult for brands to reach audiences in a highly saturated advertising environment. In this environment, product placement remains essential in reaching the target audiences due to the advantages it offers to brands compared to traditional advertisements. The aim of this study, being distinctly different from previous research, is to test the effects of attitude toward actor and character on attitude toward movies, product placement, and brand. Furthermore, it is aimed to investigate the serial mediating effect between these attitudinal constructs. The data obtained from 300 participants were analyzed with SmartPLS 3.2.8 using partial least squares path analysis (PLS-SEM). As a result, the attitude toward the actor, character, and movie has direct and indirect effects on product placement and attitude toward the brand. Furthermore, the effect of the attitude toward movies and product placement has a serial mediating effect on the relationship between the attitude toward the actor, the character and the brand.
Keywords: 650; Product Placement; Attitude; Actor; Brand; PLS-SEM